Travel Bubble and Virtual Tourism Strategies to Increase Tourist Visits - Bambang Riyadi; Giyah Yuliari; Putra Perdana (Goodwood Publishing, 2022)
Purpose: The purpose of the research is to find out the application of the Travel Bubble Strategy and Virtual Tour Package in order to increase tourist visits. The research was conducted in the Ex-Residency of Surakarta which includes the city of Solo, 6 Regencies (Boyolali, Karanganyar, Klaten, Sragen, Sukoharjo and Wonogiri). which have museums and heritage of international standard. Research Methodology: In qualitative research design, data is presented descriptively qualitatively and interpretatively. The data needed are primary data and secondary data. Data collection methods, observation and interviews, and involving informants. Data description is supported by the review of several documents, literature and related records, documentation in the form of photos or video recordings about the object of research to complete data analysis. Results: There are 2 strategies, namely Travel Bubble and Virtual Tourism to increase tourist visits to Museum and Cultural Heritage Attractions, during a pandemic that doesn't know when it will end. Limitations: The research was conducted for museums and cultural heritage that have been developed, and are known by domestic and foreign tourists. Various tourist attractions that have been developed by the region have not been offered by specialized tourist agents. Contributions: The use of travel bubble strategies and virtual tourism is one solution so that tourism activities continue to run even though there is still a threat of the covid-19 pandemic. The lives of people who depend on tourism businesses can continue well.